CORPUS LINGUISTICS: UTILIZATION OF A MORPHOLOGICAL PERSPECTIVE - Almos, Rona; Seswita, Seswita; Asdaqul Asma, Rahma (Universitas PGRI Sumatera Barat, 2024)
This research aims to examine the use of corpus linguistics from a morphological perspective. Corpus linguistics, as an empirical method that utilizes collections of texts or speech, allows researchers to carry out language analysis on a large scale with a higher level of accuracy. In the field of morphology, this approach is used to identify and analyze the frequency and distribution of morphemes, morphological variations, and distribution patterns of affixes in various linguistic contexts. Through comprehensive corpus data analysis, this research is expected to reveal morphological patterns that are not visible in small or introspective studies. The research results show that the corpus-based approach provides deeper and broader insights into the morphological structure of language, although there are several challenges such as the representativeness of the corpus and complex data processing. This research makes a significant contribution to the understanding of morphological variation and distribution and offers recommendations for a more effective corpus research methodology.